Power system analysis - Shubhanga, K. (Pearson, 2018)
Power System Analysis: A Dynamic Perspective a text designed to serve as a bridge between the undergraduate course on power systems and the complex modelling and computational tools used in the dynamic analysis of practical power systems. With extensive teaching and research experience in the field, the author presents fundamental and advanced concepts using rigorous mathematical analysis and extensive time-domain simulation results. The text also includes numerous plots with clear explanation for easy understanding.